Between culture and satisfaction: mediating roles of renqing perception and rules perception. (15th March 2020) - Ren, Han; Chen, Charles Weizheng; Chen, Yuling
Abstract : Renqing is a culturally specific Chinese notion of the informal norms in society that are significantly different from the formal rules. This paper focuses on employees' perception of renqing and of the rules in Chinese workplaces. Specifically, we define renqing (or rules) perception as the extent to which employees perceive that people's actions in their organizations follow renqing norms (or formal rules). Conceptually and empirically, we find that both renqing perception and rules perception are two‐dimensional constructs. Drawing on social information processing theory, we propose the mediating mechanisms underlying organizational culture, employees' perceptions of renqing and of rules, and their job satisfaction. Specifically, we hypothesize that clan culture will positively relate to renqing perception, while hierarchy culture will have a positive relation to rules perception; both will lead to higher job satisfaction. Results from two‐wave surveys of 325 Chinese employees provide largely consistent support for our hypotheses. Theoretical and practical implications are discussed. Key points: This paper defines two new constructs termed as renqing perception and rules perception. Perceived clan culture and hierarchy culture will positively relate to renqing perception and rules perception, respectively. Renqing perception and rules perception serve as the mediators between perceived organizational culture and job satisfaction.